Transport survey methods : best practice for decision making - Zmud, Johanna; Gosselin, Martin Lee; Carrasco, Juan Antonio (United Kingdom : Emerald Group Publishing, 2013)
This book brings together a selection of peer-reviewed papers and workshop syntheses from the 9th international conference held in Puyehue, Chile in November 2011.
Includes bibliographical references and index.
Keywords: Traffic surveys; Transportation -- Statistical methods